Michelle Obama as a Political Symbol: Race, Gender, and Public Opinion toward the First Lady. Issue 3 (September 2019) - Badas, Alex; Stauffer, Katelyn E.
Abstract: Popular commentary surrounding Michelle Obama focuses on the symbolic importance of her tenure as the nation's first African American first lady. Despite these assertions, relatively few studies have examined public opinion toward Michelle Obama and the extent to which race and gender influenced public evaluations of her. Even fewer studies have examined how the intersection of race and gender influenced political attitudes toward Michelle Obama and her ability to serve as a meaningful political symbol. Using public opinion polls from 2008 to 2017 and data from the Black Women in America survey, we examine public opinion toward Michelle Obama as a function of respondents' race, gender, and the intersection between the two. We find that African Americans were generally more favorable toward Michelle Obama than white Americans, with minimal differences between men and women. Although white women were no more likely than white men to view Michelle Obama favorably, we find that they were more likely to have information on Michelle Obama's "Let's Move" initiative. Most importantly, we find that Michelle Obama served as a unique political symbol for African American women and that her presence in politics significantly increased black women's evaluation of their race-gender group.